Last chance gulch [large type] - Rundell, B. N. (Rundell, B. N. McCain chronicles ;, 2024)
"It was a different time and place . . . the Civil War had destroyed most everything they knew. Determined to begin anew, men came west in droves, lured by the promise of riches in the goldfields. It was into this melee of madness that Elijah McCain rode, committed to fulfilling a covenant to his recently departed wife. He came from years serving as an officer in the bloodiest war to date in the fledgling United States. Now he was bound for the goldfields of Montana territory, to the new strikes in Last Chance Gulch that were said to be the richest yet. McCain had always been committed to standing for right, no matter the cause or cost, but in this hostile land, lawmen turned a blind eye while vigilantes rose up, bringing some semblance of law and order. With the devil's crowd painting the land with the blood of innocents, could he stand aside? Or would he take a stand? A lawless land is no match for a man bound by a covenant..." --